Le brocanteur de Charleville - Julien Bondaz (Contextes)
Designed as a tribute to Jean Jamin, who died on 21 January 2022, this article questions the place of literature and autobiographical writing in his works. It focuses on the patterns of disparition and memory, but also of flea market and shipwreck in his writings, and it sheds light on the importance of Arthur Rimbaud and Michel Leiris in his trajectory. It also considers the texts that Jamin published on the occasion of several famous exhibitions held at the Museum of Ethnography in Neuchâtel, showing that these texts have been privileged spaces for him to question the relationships between literature, museology and anthropology.